2021
DOI: 10.1177/10668969211014256
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomatoid Mesothelioma: A Clinicopathological and Immunohistochemical Study of 64 Cases

Abstract: Sixty-four cases of sarcomatoid pleural mesothelioma represent the basis of this study. The patients are 51 men and 13 women between the ages of 42 and 79 years, who presented with symptoms of chest pain, cough, and weight loss. Diagnostic imaging showed the presence of diffuse pleural thickening with encasement of the lung parenchyma in all the cases. All patients had surgical resection via extrapleural pneumonectomy. By immunohistochemistry, all cases were positive for cytokeratin AE1/AE3; however, reactivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Sarcomatoid mesotheliomas are composed of proliferating spindles, elongated cells with fusiform nuclei, and inconspicuous nucleoli with variable atypia arranged haphazardly in a fascicular manner. In some cases, spindle cells alternate with areas of hyalinization, whereas in others, areas of necrosis can be present 29. Desmoplastic mesotheliomas are a variant of sarcomatoid mesothelioma, in which the spindle cells usually have mild atypia and are arranged haphazardly, in a hypocellular “patternless” pattern immersed in a dense, hyalinized stroma 30–32…”
Section: Pathologymentioning
confidence: 99%
“…Sarcomatoid mesotheliomas are composed of proliferating spindles, elongated cells with fusiform nuclei, and inconspicuous nucleoli with variable atypia arranged haphazardly in a fascicular manner. In some cases, spindle cells alternate with areas of hyalinization, whereas in others, areas of necrosis can be present 29. Desmoplastic mesotheliomas are a variant of sarcomatoid mesothelioma, in which the spindle cells usually have mild atypia and are arranged haphazardly, in a hypocellular “patternless” pattern immersed in a dense, hyalinized stroma 30–32…”
Section: Pathologymentioning
confidence: 99%
“…Immunochemical profile of sarcomatoid mesothelioma is different from the epithelioid. Sarcomatoid mesotheliomas are at least focally positive for cytokeratins AE1/AE, pan-cytokeratin (OSCAR), and anti-cytokeratin clone 1(KL1), as well as cytokeratin CAM5.2 [62,68]. But sarcomatoid mesotheliomas can be cytokeratin-negative.…”
Section: Peritoneal Well-differentiated Papillary Mesothelial Tumor H...mentioning
confidence: 99%
“…But sarcomatoid mesotheliomas can be cytokeratin-negative. Sarcomatoid mesotheliomas are positive for mesothelial markers such as calretinin, WT1, and D2-40 in limited cases [62,68]. Sarcomatoid mesotheliomas are often vimentin-positive, whereas epithelioid mesotheliomas are often negative to vimentin.…”
Section: Peritoneal Well-differentiated Papillary Mesothelial Tumor H...mentioning
confidence: 99%
“…By definition, these tumors are characterized by the presence of spindle cellular proliferation with elongated nuclei and inconspicuous nucleoli. More recently, Oramas et al 21 reported 64 sarcomatoid mesotheliomas from patients who had extrapleural pneumonectomies and identified that in ~40% of the cases there was a small (< 10% of the total tumor burden) epithelioid component. The authors also noticed that nuclear atypia ranged from moderate to severe and that mitotic activity although present was not markedly increased.…”
Section: Sarcomatoid Mesotheliomamentioning
confidence: 99%
“…In contrast, reports of low survival rates in patients with sarcomatoid mesotheliomas have been reported in series exclusively with that type of mesothelioma with fatal outcomes in a period of 3 years. 21 Based on the different points of view regarding the clinical outcome and treatment options, it is possible that the best results are obtained in patients with good performance, epithelioid mesothelioma subtype without nodal disease, early pathologic stage, and treated with surgery and adjuvant or neoadjuvant therapy.…”
Section: Treatment and Clinical Outcomementioning
confidence: 99%